Identification and Quality Evaluation of Raw and Processed Asarum Species Using Microscopy, DNA Barcoding, and Gas Chromatography-Mass Spectrometry - Guangzhe Yao; Wenjuan Ma; Xuhua Huang; Qi Jia; Jiayuan Shen; Yanxu Chang; Huizi Ouyang; Jun He (Journal of Analytical Methods in Chemistry)
Asarum (Aristolochiaceae) is one of the common herbs used to relieve exterior syndromes. Some volatile components of Asarum which have toxic effect may cause adverse reactions such as headache, general tension, unconsciousness, and respiratory paralysis. Therefore, Asarum is normally processed to reduce such toxicity and adverse effects. The bioactive ingredients contained in different Asarum herbs vary significantly; this variation may be attributed to their differences in species, origins, or processing methods. In this study, 16 batches of Asarum herbs were collected, and their species were identified using DNA barcoding, which is a method for distinguishing plant species, coupled with microscopy. A gas chromatography-mass spectrometry (GC-MS) method for simultaneous determination of 10 compounds was established to evaluate the contents of raw and processed Asarum herbs. Multivariate analysis was then applied to compare different batches of herbs based on the GC-MS data. DNA barcoding identified the herbs as being derived from four sources, and herbs from different origins showed different microscopic features. The results demonstrated that most of the samples were clearly clustered into distinct groups that corresponded to species types. All raw and processed samples were classified by partial least squares discriminant analysis (PLS-DA) based on the 10 analyzed compounds. The findings suggested that safrole and methyleugenol with a variable importance in the project (VIP) > 1 are unique compounds that can be used to differentiate between Asarum species. Safrole, methyleugenol, and 2,6,6-trimethylcyclohepta-2,4-dien-1-one were identified as significant constituents, the presence of which can be used to differentiate between raw and processed Asarum samples. These results indicate that species and processing methods show important effects on the composition of Asarum herbs.